Movie selection and e-WOM preference : a cross-cultural perspective - Hao, Xiaoming (2019)
This article investigates the quantity- and quality-motivated bandwagon effects on individual movie selection from a cross-cultural perspective. Based on theories of information processing and decision making, we examined how people from different cultural backgrounds (e.g., collective versus individual and vertical versus horizontal cultural orientations) differ in their preferences of aggregate electronic word-of-mouth (e-WOM), which is related to heuristic information processing, or more detailed individual e-WOM, which is related to systematic information processing. Empirically, we relied on an online study using movie selection scenarios that were distributed to participants in Singapore, the United States, and Germany. Results indicate significant cultural differences in the preference for e-WOM and related information processing modes. The individual cultural orientations of the participants offered a better explanation of the variance than a simple country-of-origin differentiation.